Early Super Soft Source Spectra in RS Oph - J.-U. Ness (Acta Polytechnica CTU Proceedings)
Recent Swift X-ray monitoring campaigns of novae have revealed extreme levels of variability during the early super-softsource (SSS) phase. The first time this was observed was during the 2006 outburst of the recurrent nova RS Oph which was also extensively covered by grating observations with XMM-Newton and Chandra. I focus here on an XMM-Newton observation taken on day 26.1, just before Swift confirmed the start of the SSS phase, and a Chandra observation taken on day 39.7. The first observation probes the evolution of the shock emission produced by the collision of the nova ejecta with the stellar wind of the companion. The second observation contains bright SSS emission longwards of 15°A while at short wavelengths, the shock component can be seen to have hardly changed. On top of the SSS continuum, additional emission lines are clearly seen, and I show that they are much stronger than those seen on day 26.1, indicating line pumping caused by the SSS emission. The lightcurve on day 39.7 is highly variable on short time scales while the long-term Swift light curve was still variable. In 2007, we have shown that brightness variations are followed by hardness variations, lagging behind 1000 seconds. I show now that the hardness variations are owed to variations in the depth of the neutral hydrogen column density of order 25%, particularly affecting the oxygen K-shell ionization edge at 0.5 keV.